Landau-Kleffner Syndrome: IV g-Globulin Response - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
An 8-year-old girl with Landau-Kleffner syndrome failed to respond to antiepileptic drugs and steroids but showed clinical and EEG improvement after intravenous g-globulin therapies at the American University of Beirut School of Medicine, Lebanon.